Conventional and Papillary Renal Cell Carcinomas and Focal Segmental Glomerulosclerosis in a Nephrectomy. Issue 6 (November 2015) - Al-Delfi, Firas; Herrera, Guillermo A.
Abstract : Abstract: This is a case report of a 63-year-old morbidly obese (body mass index, 46.5 kg/m 2 ) African American woman with a medical history of recurrent urinary tract infections, diverticulosis/diverticulitis, duodenitis, colovesical fistula, gout, hypertension, degenerative joint disease, carpal tunnel syndrome, a 20-pack-year history of tobacco use, and bilateral axillary hidradenitis suppurativa. After multiple episodes of gross hematuria and suprapubic discomfort, a computed tomographic scan showed a solid mass in the lower pole of the right kidney. The patient underwent right open radical nephrectomy in May 2010 without major complications. A conventional (clear cell) renal cell carcinoma and a small papillary renal cell carcinoma were found upon histopathologic examination of the kidney. Examination of the nonneoplastic renal parenchyma revealed changes indicative of focal segmental glomerulosclerosis, as well as mild arterial nephrosclerosis. No tumor metastases were detected at 5 years after nephrectomy. Her serum creatinine and estimated glomerular filtration rate gradually deteriorated in the 5 years after nephrectomy. The gradual, less steep renal function deterioration of this patient emphasizes the importance of reporting nonneoplastic renal lesions/diseases in nephrectomies for kidney and renal pelvis tumors. She developed edema, progressive proteinuria reaching 6.5 g/d, and serum creatinine level of 4.2 mg/dL (baseline serum creatinine at time of nephrectomy was 0.7 mg/dL). The early diagnosis helped medically manage and delay the progression of the medical renal disorder. An easy algorithmic approach for nonneoplastic renal parenchymal tissue should be adopted by general/surgical pathologists when evaluating surgical nephrectomies.